An overview of tea research in Tanzania - with special reference to the Southern Highlands. - Carr, M. K. V.; Ndamugoba, D. M.; Burgess, Paul J.; Myinga, G. R. (Cranfield University, 1992)
The history of tea development in Tanzania from the early part of this century to the present is summarised. Average yields of made tea from well managed estates in the Mufindi district have increased from around 600 kg ha-1 in the late 1950s to 3000 kg ha-1 at the present time: by comparison, yields from smallholder farms have remained much lower, averaging only 400-500 kg ha-1. There have been a large number of technical, economic and other changes over the last 30 to 40 years. The removal of shade trees, the use of herbicides, the application of NPK compound fertilisers, the introduction of irrigation (on some estates) and changes in harvesting policy have all contributed to the increases in yield. Financial and infrastructural problems have contributed to the low yields from many smallholders and others, and have limited the uptake of new technology. The contribution of research is reviewed, from the start of the Tea Research Institute of East Africa in Kenya in 1951, through to the development of the Marikitanda Tea Research Centre in Amani in 1967; the Ngwazi Tea Research Unit in Mufindi (1967 to 1970, and from 1986), and lastly the Kifyulilo Tea Research Station, also in Mufindi in 1986. The yield potential of well fertilized and irrigated clonal tea, grown at an altitude of 1800 m, is around 6000 kg ha-1. This potential is reduced by drought, lack of fertilizer, bush vacancies and inefficient harvesting practices. The corresponding potential yields at high (2200 m) and low (1200 m) altitude sites range from 3000-3500 kg ha-1 up to 9000-10000 kg ha-1 and are largely a function of temperature. The opportunities for increasing yields of existing tea, smallholder and estate, are enormous. Tea production in the Southern Highlands of Tanzania is about to expand rapidly. Good, appropriate research is needed to sustain this development over the long term, and suggestions on how best this is done in order to assist the large scale producers as well as the smallholders, are discussed.